f(x) =x^3-2x^2-15+36
![fx x32x21536 class=](https://us-static.z-dn.net/files/d88/3978313ed29a781d64299ae739a1561b.jpg)
From the rational roots theorem we can have ±1, ±2, ±3, ±4, ±6, ±9, ±12, ±18, or ±36 as factors to this trinomial.
After checking for one factor we find that 3 works.
From long division we divide the trinomial by (x-3) since it's a factor to get:
x^2 + x -12
We can easily factor this to (x+4)(x-3)
We add in our factor we found earlier to find the factored version to be
(x-3)(x-3)(x+4)
x =3 and x = -4 are solutions to the trinomial.